Broadband electromagnetic absorbing performance by constructing alternate gradient structure (AGS) for PMMA-based foams. (October 2021) - Zhou, Danfeng; Yuan, Huan; Yu, Zirui; Guo, Wei; Xiong, Yuanlu; Luo, Guoqiang; Shen, Qiang
Abstract: The PMMA-based composites with CNTs sheets were alternate arranged to fabricate the foam with alternate gradient structure (AGS) via the one-step physical constraint foaming technology. The influence of AGS structure on electromagnetic waves absorbing (EMA) properties of foam were detailed study. The theoretically calculated and directly tested results present that comparing with the normal single-layer foam, the absorbing bandwidth of the foam with AGS broadens to 3.2 GHz (8.8–12.0 GHz) and the minimum reflection loss decreases to −30.2 dB at the same CNTs content. This enhancement is attributed to AGS, which improves the impedance matching of foams while triggers multiple reflection of electromagnetic waves and intensifies interfacial polarization loss among the layer interfaces, as well as conductive loss of CNTs network, endowing outstanding dissipation capability of the foam with AGS. It provides an effective way to design and fabricate light weight and good EMA materials.